Towards Effective Enforcement of Uncontested Monetary Claims : Lessons from Eastern and Central Europe - World Bank Group; Netherlands Ministry of Foreign Affairs (World Bank, Washington, DC, 2017)
This comparative analysis examines the enforcement of uncontested monetary claims in the EU-11, as well as in FYR Macedonia (hereinafter "comparator countries"), and outlines options available to policymakers. The users of this analysis will be policymakers in environments that are strained by backlogs of such claims. Primarily, these will be Western Balkans countries, especially those of the former Yugoslavia. The analysis may also benefit policymakers elsewhere who wish to improve enforcement of uncontested claims. When exploring enforcement of uncontested claims, the report gives particular attention to utility bills since they form a significant portion of such claims. Additionally, enforcement of utility bills is a sensitive policy matter due to the social significance of these services. Uncontested claims are enforced in two stages: first, obtaining enforceable title; and second, execution of the enforceable title. In all comparator countries, these two stages are carried out by two different authorities. None of the comparator countries have chosen to combine the two stages. In contrast, in Serbia and in Montenegro these two stages form part of a single enforcement procedure carried out by an enforcement agent.